Cumulative Deceleration Area: A Simplified Predictor of Metabolic Acidemia. Issue 4 (April 2022) - Furukawa, Abby; Neilson, Duncan; Hamilton, Emily
Abstract : (Abstracted from J Matern Fetal Neonatal Med 2021;34:3104–3111) Electronic fetal heart rate (FHR) monitoring is a mainstay of intrapartum clinical care, despite low agreement on the value of key elements of tracing analysis among obstetricians. The degree of heart rate variability and type of deceleration are used as etiologic indicators of the hypoxic injury driving deceleration but rely on subjective interpretation.